Comparison of the unfair competition rules under the light of draft Turkish commercial code and EU regulations - Gezer, Çağlar (My University, 2009)
Serbest sanayi ve ticaret kuralı şirketlere rekabet serbestisi sağlamakta ve bu serbesti zaman zaman şirketler arasında haksız rekabete yol açabilmektedir. Farklı olmalarına rağmen, tüm Avrupa ülkeleri, ticari faaliyetleri kontrol altında tutabilmek amacıyla, doğruluk kuralı üzerine kurulu mekanizmalar geliştirmiştir. İştirakçilerin, menfaatleri doğrultusunda dürüst bir şekilde hareket etmeleri gerektiği kabul edildiğinden, bu dürüstlüğü sağlayabilmek amacıyla bazı kurallar konusunda anlaşmaya varılmalıdır. Ülkeler arasında uluslararası ticaret serbestisi ve tüketicinin en üst düzeyde korunması amacıyla, Avrupa Birliği Hukuku kapsamında bazı hukuki düzenlemeler yapılmıştır. Bu tez ile yönetmelikler ve yönergeler üzerine odaklanılarak, Avrupa Birliği ve Türkiye’de haksız rekabet hukukunun uygulamasına ilişkin olarak, iki bölüm altında kapsamlı bir çalışma sunulmaktadır.

Fundamental principle of freedom of commerce and industry gives companies rise the freedom of competition and this freedom may sometimes cause unfair commercial practices between the companies. Despite differences, all countries in Europe have set up mechanisms based on the principle of fairness in order to control activities related to commerce. It is generally believed that the market should act in a fair way towards the interests of all participants and therefore that some rules should be agreed in order to secure such fairness. In order to combine a high level of consumer protection with freeing up international trade in all countries, some regulations are entered into force in the European Union Law. This thesis introduces a comprehensive outline of unfair competition law in the European Union and Turkey under two chapters by way of focusing on regulations and directives
Keywords: Avrupa Birliği Hukuku; Haksız Rekabet Hukuku; Türk Hukuku